Application of Integrated Dynamic Archival Information System (SRIKANDI) in Supporting Good Governance at the Office of Education and Culture of Mojokerto City - Firmansyah, Oktavia Maharani Yuli; Hariyono, Catrina Agustin; Puspasari, Durinda (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
The government has utilized technology to improve efficiency, effectiveness, and transparency in public administration in the era of rapid advances in communication and information technology. This study aims to analyze the application of the Integrated Dynamic Archive Information System Application (SRIKANDI) in supporting Good Governance at the Mojokerto City Education and Culture Office. The research method used is descriptive with a qualitative approach, with data sources comprising primary and secondary data obtained through purposive sampling. Data collection methods include interviews and documentation, with data analysis techniques employing the Miles and Huberman model. Data validity testing is conducted using source triangulation. The results showed that the SRIKANDI application made a significant contribution in improving the efficiency, effectiveness and timeliness of correspondence administration. Features such as automatic logging, structured disposition, and digital signatures enhance transparency and accountability, while flexible access supports increased productivity. Despite technical challenges such as digital errors and network disruptions, the app's positive impact in realizing a paperless office and online correspondence is highly visible. Therefore, it is recommended to continue conducting training and socialization to optimize understanding and use of this application, as well as making technical improvements to overcome existing obstacles for better administrative performance.